Живопис Волині. Жінки-художниці кінця ХХ — початку ХХІ сторіччя - Прокопович, Тетяна Анатоліївна; Prokopovych, Tetiana A. (My University, 2017)
У статті проаналізовано стилі і напрямки творчих здобутків жінок-художниць Волині кінця ХХ — початку ХХІ ст., які є членами НСХУ. Виявлено два основних напрямки творчості: живописний і декоративний. Мистецьке надбання Волині в живописній манері виконання наповнюється роботами С. Байдукової, Т. Галькун, Г. Івашків, О. Свіжак, Л. Спаської та ін. Указані художниці у своїх роботах дотримуються академізму, реалістичності форм, живописності, зображаючи пейзажі, натюрморти, портрети, сюжетно-тематичні композиції. Натомість мистецьке надбання в декоративній манері виконання наповнюється роботами мисткинь О. Бурдаш, О. Кучми, Т. Мялковської, Т. Ядчук-Богомазової, О. Ядчук-Мачинської та ін., твори яких тяжіють до символізму, спрощених форм, знаковості, наповнені архаїчними елементами, забутими символами. На основі аналізу творчого здобутку було виявлено спільну рису і особливість малярства на Волині кінця ХХ — початку ХХІ ст. — наявність національних мотивів у сюжетній лінії.В статье проанализированы стили и направления творческих достижений женщин-художниц Волыни конца ХХ — начала ХХI в., которые являются членами НСХУ. Выявлено два основных направления творчества: живописный и декоративный. Художественное достояние Волыни в живописной манере наполняется работами С. Байдуковой, Т. Галькун, Г. Ивашкив, О. Свижак, Л. Спаской и др. Эти художницы в своих работах придерживаются академизма, реалистичности форм, живописности, изображая пейзажи, натюрморты, портреты, сюжетно-тематические композиции. Художественное достояние в декоративной манере живописи наполняется работами таких художниц, как О. Бурдаш, О. Кучма, Т. Мялковской, Т. Ядчук-Богомазовой, А. Ядчук-Мачинской и др., произведения которых тяготеют к символизму, упрощенным формам, знаковости, они наполнены архаичными элементами, забытыми символами. На основе анализа творческого достояния была обнаружена общая черта и особенность живописи на Волыни конца ХХ — начала ХХI в. — наличие национальных мотивов в сюжетной линии. The article analyzes styles and areas of creative achievements of Volyn women artists who are members of the National Union of Artists of Ukraine. The existence of several approaches to solving the problem of covering of the life and career of artists has been studied. The objectives of this study are to systematize the creative achievements of Volyn women artists during the late XX – early XXI century which are presented by NUAU. These include: S. Baydukova, O. Burdash, T. Halkun, G. Ivashkiv, L. Spaska, O. Kuchma, T. Myalkovska, O. Svizhak, O. Yadchuk-Machynska, T. Yadchuk-Bohomazova. There are many varieties in styles and genres of painting and each artist has her own styles and genres, which she uses to depict her outlook. Theoretical and methodological analysis of the problem of research of Volyn women artists’ creativity of the late XX – early XXI century made it possible to detect a problem such as lack of consistency in studying the artistic heritage of Volyn artists of the late XX – early XXI century. Based on the reviewed scientific papers and publications it was revealed that the research and promotion of art in the Volyn region, including contemporary artists are dealt by Art Museum. Lutsk, “Gallery – IX” and “Art Gallery Volyn.” As a result of the systematic study of styles and areas of artists’ creative achievements of the late XX – early XXI century two main areas in which women artists are developing and working were reviled – pictorial and decorative. Artistic heritage of Volyn in the pictorial manner of performance is filled with works of artists such as S. Baydukova, T. Halkun, H. Ivashkiv, O. Svizhak, L. Spaska and others. In the pictorial area female artists stick to academism, realistic forms and picturesqueness, while depicting landscapes, still lives, portraits and plot topical compositions. While the artistic heritage of Volyn in a decorative manner of performance is mostly filled with the works of women artists such as A. Burdash, O. Kuchma, T. Myalkovska, T. Yadchuk-Bohomazova, O. Yadchuk-Machynska and others. In decorative area, artists tend to symbolism, simplified forms, signification, using archaic elements in their works, finding forgotten symbols. Analyzing the creative achievements of artists it seems that the artists are beyond the society, coexisting in different dimensions of information, transferring the expression of their emotions on canvas. Still lives, wildflowers, mushrooms are favorite themes in paintings of S. Baydukova. T. Halkun – is one of the few artists who tried to hold up in the memory of posterity the unique beauty of Volyn (series of works “Disappearing Polesie”, “Lesya Ukrainka’s paths”). O. Burdash seeks for harmony through original vision of people depicting them like mystical beings who tell their stories on canvases. H. Ivashkiv presents her mental world of harmony in the works which are filled with light and color. Light, soft and rich range of paintings affects by its color purity. Perfection and skills of the artist can be seen in its technique, she depicts the play of light, colors and shapes with several brush strokes. One of the characteristics of composite solution of G. Ivashkiv is a rhythmic repeatability of certain elements, giving the picture a special sound. O. Kuchma uses hot batik technique to create thematic composition with stylized and decorative images that clearly identifies her personality on the territory of the art space. Original and unique world of T. Myalkovska comes to life through painting on glass and boards, batik technique and various installations, which borders on childish spontaneity and simplicity, but has a clear professional background. Calm colors and academism – are the main features of the works of art of O. Swiezak. In her works, the artist draws attention to light, color, plastics, playing of light and shadow on objects. Portraits, still lives and landscapes reveal the artist’s skill. L. Spaska created sacred works of art on her monumental and easel paintings of the twentieth century, describing temples and drawing portraits of famous people of the time. T. Yadchuk-Bohomazova reveals the expression of her emotions through the semantics of signs and symbols on batik paintings and tapestries, creating a new trend in the modern style of decorative art. O. Yadchuk-Machynska portrays her life philosophy on paintings through experimentation with different techniques and materials. Styles and genres the artists work with are quite individual. We can conclude that the Volyn artists of the late XX – early XXI century operate and develop their creativity mainly in two main areas – pictorial and decorative. In a pictorial area artists tend to academism and realistic forms, while depicting landscapes, still lives, portraits, plot topical compositions. On the other hand, decorative area painters tend to symbolism, simplified forms and symbolism using archaic elements and rediscovering forgotten symbols in their works. By analyzing the creative achievements of Volyn women artists of the late XX – early XXI century it is revealed that one of the common traits and characteristics of contemporary painting in Volyn region is the presence of national motives in the storyline, the identity of individual artists is made through images, symbols, colors and dynamics in the paintings. Artistic heritage of all artists contains scenes that are directly related to Ukraine, Volyn. In the first group of artists it is manifested through depicting landscapes of Polissia, Volyn and other everyday items. Those artists who adhere decorative area, it is shown by depicting Ukrainian symbols, which are transmitted through the ages.
Volyn Paintings. Women artists of the late XX – early XXI century
Живопись Волыни. Женщины-художницы конца ХХ — начала ХХІ столетия
Keywords: мистецтво; живопис; сучасне мистецтво; художники; Волинь; искусство; живопись; современное искусство; художники; art; painting; modern art; artists; Volyn